2015
DOI: 10.17363/sstb.20151714050
|View full text |Cite
|
Sign up to set email alerts
|

Sports and Self-Esteem Relationship in High-School Students

Abstract: Öz: Spor yapan ve yapmayan lise öğrencilerinin özgüvenleri arasında anlamlı bir fark olup olmadığını saptamayı amaçlayan ve bu amaç doğrultusunda ayrıca cinsiyet, okul türü, sınıf, spor sıklığı, spor madalya ve spor takım değişkenlerinin öğrencilerin özgüvenlerinde anlamlı bir farklılığa neden olup olmadığını inceleyen bu çalışma genel tarama modeli ile gerçekleştirilmiştir. Bu araştırmanın çalışma grubunu İstanbul'daki değişik türden liselerde okumakta olan 230 öğrenci oluşturmaktadır. Bu çalışmada veri topla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It can be said that while students are studying at the high school level, they become more self-confident as the grade rises. When the literature was examined, Arslan et al (2015) concluded in their study that as the grade level increases, the level of internal confidence increases. In this context, the results of the present study show similarity.…”
Section: Discussionmentioning
confidence: 99%
“…It can be said that while students are studying at the high school level, they become more self-confident as the grade rises. When the literature was examined, Arslan et al (2015) concluded in their study that as the grade level increases, the level of internal confidence increases. In this context, the results of the present study show similarity.…”
Section: Discussionmentioning
confidence: 99%